Media Freedom and Corruption in Different Countries of the World - Dr. Aboutrab Talebi, Dr. Farshad Momeni, Esmaeil SHojaei, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aimed at examining the effect of media freedom on corruption reduction. Media serve as platforms for public supervision over the government and sovereignty of every country provided freedom of media. Regarding the comparison of corruption level and media freedom all around the world, the statistical population of extant paper comprised all countries of the world. Sampling was done based on the available information and data, and then 30 countries were chosen and assigned to three groups with high-level, moderate, and low-level corruption over the period 2012-2019. The required data were collected from databases of international institutions working on corruption and media freedom. Data analysis was done through a panel data model, as well as Chow and Hausman Test. Results indicated a significant and reverse effect of media freedom on corruption in different countries of the world. Moreover, media freedom had a higher effect on corruption in those countries with low-level corruption